Applying legitimacy theory to understand sustainability reporting behaviour within South African integrated reports. (4th May 2022) - Herbert, Shelly; Graham, Mark
Abstract : Sustainability disclosures are frequently included within integrated reports, in order to provide disclosures relating to the capitals identified in the International Framework (the Framework). South Africa has been at the forefront of integrated reporting, following the guidance of King III and subsequently the Framework. This study draws on data previously presented by the authors, and identifies the relationships and correlation between the application of principles from the Framework, such as materiality and conciseness, as well as the total number of sustainability disclosures and the industry classification, age and size of the companies, through the lens of legitimacy theory. The study uses data collected through interpretive content analysis of the integrated reports of South African companies in 2011 and 2015, as well as company metrics, which are analysed using Spearman's rank correlation and a k-means cluster analysis. The results reveal that companies tend to consistently apply the principles from the Framework, and the size of the company was not consistently correlated. However, the age of the company was correlated to the materiality of disclosures provided. The findings are consistent with legitimacy theory and add to the legitimacy theory literature by identifying the sustainability reporting behaviour displayed by companies of various sizes, ages and industry classifications.